Parasite co-infections show synergistic and antagonistic interactions on growth performance of East African zebu cattle under one year - Thumbi, Samuel M.; Bronsvoort, B.M. de C.; Poole, Elizabeth J.; Kiara, Henry K.; Toye, Philip G.; Ndila, M.; Conradie, I.; Jennings, A.; Handel, Ian G.; Coetzer, Jacobus A.W.; Hanotte, Olivier H.; Woolhouse, Mark E.J. (Cambridge University Press, 2013)
The co-occurrence of different pathogen species and their simultaneous infection of hosts are common, and may affect host health outcomes. Co-infecting pathogens may interact synergistically (harming the host more) or antagonistically (harming the host less) compared with single infections. Here we have tested associations of infections and their co-infections with variation in growth rate using a subset of 455 animals of the Infectious Diseases of East Africa Livestock (IDEAL) cohort study surviving to one year. Data on live body weight, infections with helminth parasites and haemoparasites were collected every 5 weeks during the first year of life. Growth of zebu cattle during the first year of life was best described by a linear growth function. A large variation in daily weight gain with a range of 0·03–0·34 kg, and a mean of 0·135 kg (0·124, 0·146; 95% CI) was observed. After controlling for other significant covariates in mixed effects statistical models, the results revealed synergistic interactions (lower growth rates) withTheileria parvaandAnaplasma marginaleco-infections, and antagonistic interactions (relatively higher growth rates) withT. parvaandTheileria mutansco-infections, compared with infections withT. parvaonly. Additionally, helminth infections can have a strong negative effect on the growth rates but this is burden-dependent, accounting for up to 30% decrease in growth rate in heavily infected animals. These findings present evidence of pathogen–pathogen interactions affecting host growth, and we discuss possible mechanisms that may explain observed directions of interactions as well as possible modifications to disease control strategies when co-infections are present.